2019
DOI: 10.1177/0886260519867151
|View full text |Cite
|
Sign up to set email alerts
|

Examining Depression Among Perpetrators of Intimate Partner Homicide

Abstract: Male depression has been recognized as an important factor in some cases of intimate partner violence but there is a paucity of literature connecting depression and intimate partner homicide (IPH). This retrospective study provides a preliminary analysis that distinguished depressed from nondepressed perpetrators of IPH from a sample of 135 cases analyzed by a coroner’s homicide death review committee in Ontario, Canada. Depressed perpetrators were more likely to commit homicide-suicide and had almost 1.5 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 60 publications
0
5
0
1
Order By: Relevance
“…More general research into domestic abuse and IPH, primarily outside of the UK, has found links between perpetrators and depression (Cheng & Jaffe, 2019), previous violence within intimate relationships (Campbell et al., 2007), the use of threats of death (Cunha & Gonçalves, 2019), having direct access to a gun (Campbell et al., 2003; Spencer & Stith, 2020). Research has also found that victims of IPH have often recently left their abusive partner at their time of death (Brady & Hayes, 2018; Campbell et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More general research into domestic abuse and IPH, primarily outside of the UK, has found links between perpetrators and depression (Cheng & Jaffe, 2019), previous violence within intimate relationships (Campbell et al., 2007), the use of threats of death (Cunha & Gonçalves, 2019), having direct access to a gun (Campbell et al., 2003; Spencer & Stith, 2020). Research has also found that victims of IPH have often recently left their abusive partner at their time of death (Brady & Hayes, 2018; Campbell et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that perpetrators of IPH are more likely to be of older age (Loinaz et al, 2017;Caman et al, 2017) have less persistent criminal histories, be less socially disadvantaged (Loinaz et al, 2017;Caman et al, 2017) and show higher levels of suicidal ideation (Caman et al, 2017;Cunha & Gonçalves, 2019) More general research into domestic abuse and IPH, primarily outside of the UK, has found links between perpetrators and depression (Cheng & Jaffe, 2019), previous violence within intimate relationships (Campbell et al, 2007), the use of threats of death (Cunha & Gonçalves, 2019), having direct access to a gun (Campbell et al, 2003;Spencer & Stith, 2020). Research has also found that victims of IPH have often recently left their abusive partner at their time of death (Brady & Hayes, 2018;Campbell et al, 2003).…”
mentioning
confidence: 99%
“…Alternatively, female partners may have stayed in relationships because they believed that the intervention would be effective. Male intervention participants were more likely to be challenged in their beliefs, and increased realisation and responsibility for previous abuses may have caused considerable mental distress and feelings of shame, causing increased risk of depression, selfharm and suicide, or femicide-suicide (51,52). Researchers could miss serious abuse occurring for partners of control participants if they did not report information, as reporting and multiagency working increased the information known about partners of intervention participants.…”
Section: Discussionmentioning
confidence: 99%
“…Compare IPH and IPH-S appears to be challenging; however, some fundamental differences seem to emerge: IPH-S perpetrators appear to be less likely to have a previous criminal record or history of disregard and violations of the law ( Vatnar et al, 2019 ), using much less violent and more premeditated methods ( Jensen et al, 2009 ). Other studies concluded that IPH-S perpetrators have a higher prevalence of mental illness histories (e.g., depression; Cheng & Jaffe, 2019 ; Jensen et al, 2009 ; Zeppegno et al, 2019 ) and have used mental health services ( Campbell et al, 2007 ). Regarding the sociodemographic characteristics, IPH-S perpetrators seem to be mainly native-born citizens and more educated ( Vatnar et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%